Ayurveda Management of Herpes Zoster Ophthalmicus (HZO) - A Case Report - Samir Girde; Mamata Nakade; Sachin Chandaliya; Pranesh Gaikwad; Harshad Gulhane (Journal of Ayurveda and Holistic Medicine (JAHM), 2026)
Background: Herpes zoster (HZ) is caused by reactivation of the Varicella Zoster Virus (VZV). When the ophthalmic division of the trigeminal nerve is involved, the condition is termed Herpes Zoster Ophthalmicus (HZO). HZO is an ophthalmic emergency that may result in serious ocular complications, including vision loss, if not treated promptly. Clinical Findings: A 31-year-old male with recently diagnosed Herpes Zoster Ophthalmicus and diabetes mellitus presented to the outpatient department with painful vesicular eruptions, swelling, redness, and burning sensation over the right forehead and periocular region. Based on Ayurvedic clinical assessment, the condition was diagnosed as Visarpa. Intervention: The patient was managed with Jalaukavacharana (leech therapy), Pittaghna local applications, and individualized internal Ayurvedic medications while continuing the prescribed anti-diabetic treatment. Outcome: The patient showed marked clinical improvement with complete resolution of swelling, redness, and burning sensation, along with satisfactory healing of the skin lesions. No ocular complications or post-herpetic neuralgia were observed during the follow-up period. Conclusion: This case suggests that an integrative Ayurvedic management approach may be beneficial as an adjunctive treatment for Herpes Zoster Ophthalmicus. Early intervention was associated with favorable clinical recovery and the absence of major complications in this patient. However, larger controlled studies are required to establish the safety and effectiveness of this approach.